1990
DOI: 10.1104/pp.94.3.1488
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a cDNA Clone for α-Amylase in Mung Bean Cotyledons

Abstract: A cDNA was isolated that codes for a-amylase in mung bean (Vigna radiata) cotyledons, and the nucleotide sequence was determined. The deduced amino acid sequence (421 amino acid residues) is about 65% homologous with those of barley a-amylases. By comparing the deduced sequence with the sequence of the purified a-amylase, it was inferred that 23 Nterminal amino acids of a nascent polypeptide represent a signal peptide. Northern blot analysis showed that the levels of a-amylase mRNA are in parallel with the act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…The design of these primers was based on the following two criteria: (i) both primers correspond to highly conserved regions in the a-amylase genes and (ii) the PCR products for the AmyA and AmyB genes could be easily resolved by polyacrylamide gel electrophoresis. The two mung bean a-amylase gene primers were based on the previously published sequence information (30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The design of these primers was based on the following two criteria: (i) both primers correspond to highly conserved regions in the a-amylase genes and (ii) the PCR products for the AmyA and AmyB genes could be easily resolved by polyacrylamide gel electrophoresis. The two mung bean a-amylase gene primers were based on the previously published sequence information (30).…”
Section: Methodsmentioning
confidence: 99%
“…Since zymograms do not resolve the a-amylase isozymes of rice into distinct high and low pI groups (2,19), it has been difficult to relate these isozymes to those observed in barley and wheat. Subsequently, Huang et al (20) used DNA-DNA hybridization to classify 30 rice genomic clones into five hybridization groups. These five groups were eventually consolidated into three subfamilies (Amyl, Amy2, and Amy3) on the basis of protein comparisons to other wheat and barley a-amylase genes (8,(20)(21)(22).…”
mentioning
confidence: 99%
“…respectively (9,34,35,46,56 (6). Furthermore, NE2 of His 201 from the Lys-His-Z motif in PPA forms a hydrogen bond with sugar OH-2 in subsite ϩ1, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A conserved region in the ␤-␣ loop extending at the C terminus of the fourth ␤-strand of the (␤/␣) 8 -fold is interpreted to play an important role in the specificity (25, 27, 30 -32). Remarkably, Arg 183 -Gly 184 -Tyr 185 at this loop in AMY1 is distinctive to plant ␣-amylases; others have Lys-His-Z, where Z is hydrophobic (9,25,27,(33)(34)(35). Arg 183 in AMY1 aligns with Lys 182 in AMY2 (9), which in the crystal structure of AMY2-acarbose (71) forms a hydrogen bond to OH-3 of the sugar ring at subsite ϩ2 and in the crystal structure of AMY2-BASI (36) interacts with a glu-…”
mentioning
confidence: 99%
“…7) In leguminous plants, a-amylase is expressed in cotyledons during seed germination, where its mRNA was isolated. [8][9][10] The a-amylase is localized in lytic vacuoles in cotyledon cells, and starch granules are transported into the vacuoles via an autophagic process, and hydrolyzed there. 11) An Arabidopsis mutant suggested that one of the a-amylases in the plant is responsible for degradation of transitory starch in chloroplasts.…”
mentioning
confidence: 99%